Matching energy of unicyclic and bicyclic graphs with a given diameter. Issue 2 (30th August 2014) - Chen, Lin; Liu, Jinfeng; Shi, Yongtang
Abstract : Gutman and Wagner proposed the concept of matching energy (ME) and pointed out that the chemical applications of ME go back to the 1970s. Let G be a simple graph of order n and μ 1, μ 2, …, μ n be the roots of its matching polynomial. The ME of G is defined to be the sum of the absolute values of μ i ( i = 1, 2, …, n ) . In this article, we characterize the graphs with minimal ME among all unicyclic and bicyclic graphs with a given diameter d. © 2014 Wiley Periodicals, Inc. Complexity 21: 224–238, 2015